2013
DOI: 10.15376/biores.8.4.5067-5082
|View full text |Cite
|
Sign up to set email alerts
|

Torrefaction Kinetics of Red Oak (Quercus rubra) in a Fluidized Reactor

Abstract: a Different kinetic models have been proposed to characterize torrefaction of biomass, demonstrating dependencies on the raw material, experimental system, reaction time, and temperature. Conventionally, stationary processes have been used for kinetics studies of the torrefaction process. In this research, the torrefaction of red oak (Quercus rubra) in a bench-scale fluidized reactor was studied with emphasis on determining the kinetic parameters and improving the final material energy density. Mass loss and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Besides wood, torrefaction of several biomass types such as bamboo (Rousset et al 2011), wheat straw (Shang et al 2013), rice straw (Huang et al 2012), sewage sludge (Atienza-Martinez et al 2013), and red oak (Carrasco et al 2013) have been studied extensively. Torrefaction experiments with different biomass samples have shown that torrefaction provides solid hydrophobic fuel with reduced moisture content (Felfri et al 2005;Sadaka and Negi 2009), increased energy density (Prins et al 2006a;Yan et al 2009;Rousset et al 2011), and increased higher heating value (HHV) (Bridgeman et al 2008;Couhert et al 2009;Deng et al 2009;Yan et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Besides wood, torrefaction of several biomass types such as bamboo (Rousset et al 2011), wheat straw (Shang et al 2013), rice straw (Huang et al 2012), sewage sludge (Atienza-Martinez et al 2013), and red oak (Carrasco et al 2013) have been studied extensively. Torrefaction experiments with different biomass samples have shown that torrefaction provides solid hydrophobic fuel with reduced moisture content (Felfri et al 2005;Sadaka and Negi 2009), increased energy density (Prins et al 2006a;Yan et al 2009;Rousset et al 2011), and increased higher heating value (HHV) (Bridgeman et al 2008;Couhert et al 2009;Deng et al 2009;Yan et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…, Carassco et al . was investigated for this study. The reaction mechanism was assumed to be a one‐step process, wherein the reactivity of hemicellulose was considered while the cellulose and lignin content of biomass was found to be least reactive in the given torrefaction range .…”
Section: Resultsmentioning
confidence: 99%
“…The present model was more successful for volatilization kinetics ( r 2 = 0.98) as than in comparison to that of charification ( r 2 = 0.91). The activation energy determined in this study is reported along with the studies performed by other researchers in Table , although the model, pathway, raw material, and experimental device employed were different . As an extension of work, we are currently developing the gasification technology of entrained flow gasifier with the torrefaction as a pretreatment step for the production of synthesis gas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of k for Oxytree is challenging to compare with the literature because it depends to a large extent on the kinetic model used to determine it. For example, depending on the test method, the k value for 300 °C for oak wood was in the range from 31 × 10 −5 s −1 to 121 × 10 −5 s −1 [52]. Similarly, the activation energy is estimated for the whole torrefaction process [53,54].…”
Section: Discussionmentioning
confidence: 99%